Technostress and its management in the digital era - Dangwal, Kiran Lata (University News)
In this digital era and fast changing technology self-regulation is becoming a big challenge. We always remain glued to our phone and because of this technological developments and increasing demands, we may have a serious impact on our mental health and we may become victim of technostress. The technology has made everything work with speed such as fast processing, electronic records, synchronous and advanced communication systems, video-audio conferencing, emailing, instant messaging and social networking which have enabled a high level of communication resulting in optimisation of time and minimising the space. Although the professional sectors such as tele-medicine, tele-education, tele-consultancy are changing rapidly but this growth has not been without a darker side of the technology. The social media platform and ICT crossing all boundaries and barriers of time and space. The digitalisation has changed the very perspective of life with increasing technostress amongst us.
Keywords: Technostress, Technological developments, Stress, Stress management